Treading a Path for Effective Renewable Energy Regulation in Nigeria: Lessons from Brazil - Odebala, Victor Junior (ABUAD Law Journal, 2023)
Rising temperatures, rising sea levels, droughts and other climate change induced variants are mounting pressure on national governments to reassess their commitment to global climate change goals and their general approach to energy production and consumption within their territories. Renewable energy has become a recurring theme in the drive towards attaining clean energy and maintaining a sustainable culture. Failing to reconcile with this reality will result in negative environmental, as well as economic consequences on any nation, as less and less investment are being made in conventional energy sources. This paper aims to assess Nigeria’s current attitude to renewable energy development from the perspective of the nation’s regulatory framework. Using a comparative analysis methodology, it finds the presence of an indirect and inefficient regulatory regime on renewable energy in the country. It compares this to Brazil’s regulatory regime where it finds a comprehensible and direct regulatory structure. It asserts that the success of the Brazilian renewable energy integration is attributable to the presence of a detailed energy licensing process, direct legislation, supported research and development scheme and adequate market strategy for renewable energy. Recommendations were made along this line for more efficient renewable energy regulation in Nigeria.